2003
DOI: 10.1525/aa.2003.105.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Global and Area Studies: Insights from Caribbeanist Anthropology

Abstract: Recently, there has been an upsurge in the critical attention directed toward the area studies research paradigms that were institutionalized after World War II. This upsurge comes at a time when anthropologists are also developing increasingly sophisticated accounts of the intersections of global and local processes. Yet there has been less engaged consideration of the agendas propelling global studies over area studies curricula. In this essay, we argue that an analysis of the Caribbean and Caribbeanist anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 66 publications
0
26
0
1
Order By: Relevance
“…Following Philpott's work, a large number of studies (see Slocum and Thomas, 2003) have documented the key role of migration in Caribbean culture and society. They have shown that most people do not view migration as a means of leaving home with the intent to settle in another place, but rather as a resource that makes it possible for them to explore various opportunities abroad and enjoy social mobility, while remaining part of their Caribbean home community of origin.…”
Section: Mobility and Transnational Relationsmentioning
confidence: 99%
“…Following Philpott's work, a large number of studies (see Slocum and Thomas, 2003) have documented the key role of migration in Caribbean culture and society. They have shown that most people do not view migration as a means of leaving home with the intent to settle in another place, but rather as a resource that makes it possible for them to explore various opportunities abroad and enjoy social mobility, while remaining part of their Caribbean home community of origin.…”
Section: Mobility and Transnational Relationsmentioning
confidence: 99%
“…Since Constance Sutton's declaration that the Caribbean community in New York represents a transnational sociocultural system (Sutton 1987;Thomas-Hope 1988), the flexibility and cross border movements of Caribbean peoples have come to represent an archetype for the contemporary moment of globalization (Cohen 1998;Hannerz 1996;Khan 2001;Slocum and Thomas 2003;Trouillot 1992;Yelvington 2001). Much of the groundbreaking work concerning the nature and dynamics of transnationalism progressed with insights gained from studies of Caribbean migration (Glick Schiller, Basch, and Szanton Blanc 1992;Basch, Glick Schiller, and Szanton Blanc 1994;Pessar 1997).…”
Section: Heather Horstmentioning
confidence: 99%
“…Within Caribbean Studies (and Caribbeanist anthropology more specifically), the body of literature on nationalism, independence, and postcolonialism in the Caribbean has indeed been extensive (see Slocum and Thomas 2003 for further elaboration of various dimensions of this research). Contemporary research has not only been attentive to the ways debt agreements and new global trade and labor arrangements have transformed nationalisms throughout much of the postcolonial Caribbean but have also analyzed how race and culture articulate within attempts to construct nationalist subjectivities identified as modern (Segal 1994;Carnegie 2002;Munasinghe 2001;Godreau 2002) and how these articulations are expressed through performance and popular culture both among Caribbean populations within the region and those in diaspora (Ramos-Zayas 2003;Thomas 2004).…”
Section: Ana Yolanda Ramos-zayas and Deborah Thomasmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Caribbean, this situation is heightened by the region's global orientation throughout its history, particularly since the sixteenth century (Amit, 2001). Although Caribbeanist anthropology has been concerned with global/local articulations (Slocum and Thomas, 2003), a comparative approach to the study of island tourism specifically has been less explored (but see Ballerino Cohen, 1998).…”
Section: Introductionmentioning
confidence: 99%